High Mechanical Strain of Intervertebral Disc Cells Promotes Secretion of Inflammatory Factors Associated with Disc Degeneration and Pain. (May 2014) - Rosenzweig, D. H.; Gawri, R.; Krock, E.; Ouellet, J. A.; Stone, L. S.; Quinn, T. M.; Haglund, L.
Introduction: Low back pain is a debilitating disorder affecting a multitude of people and is currently ranked sixth among costliest treatable chronic illnesses. 1 Low back pain is often attributed to intervertebral disc (IVD) degeneration. Increased inflammatory cytokines, loss of resident cell populations, altered biomechanics, uneven loading of the spine and excessive mechanical stretch of tissue and cells are often associated with degeneration. 2 However, the mechanical and molecular mechanisms underlying disc degeneration remain poorly understood. Excessive mechanical loading of IVDs is thought to alter matrix properties and influence disc cell metabolism, contributing to degenerative disc disease and development of discogenic pain. Very little is known, however, about how mechanical strain induces these changes. This study investigated the cellular and molecular changes as well as which inflammatory receptors and cytokines were upregulated in human IVD cells exposed to high mechanical strain (HMS). The impact of these metabolic changes on neuronal differentiation was also explored to determine a role in the development of disc degeneration and discogenic pain. Materials and Methods: Cell Isolation Three consented human lumbar spines were harvested. Five were obtained (age range 19-22, mean 20.5). IVDs were separated from the adjoining vertebral body with a scalpel and divided into nucleus pulposus (NP) and the inner annulus fibrosus (AF). Cells were enzymatically isolated from the separated regions and cultured as previously described. 3 High Mechanical Strain Culture medium was replaced with serum-free media, and isolated human IVD cells were exposed to HMS (20% cyclical stretch at 0.0001 Hz for 8 hours/day over 2 days) on high-extension silicone rubber dishes coupled to a mechanical stretching apparatus 4 and compared with static control cultures. Conditioned media was collected and RNA was extracted from cells using TRIzol, and cDNA was generated. Quantitative PCR Gene expression of toll-like receptors (TLR2 and TLR4), nerve growth factor (NGF) and tumor necrosis factor-α (TNF-α) was assessed using TaqMan array probes and a 7500 Fast Real Time system (Applied Biosystems) and the ΔΔCt method. 18s ribosomal RNA was used as the endogenous control. Cytokine Arrays Collected conditioned media was analyzed for 23 common inflammatory cytokines using commercially available array blots according to manufacturer's instruction (RayBiotech Inc, Norcross, GA). Chemiluminescence detection was performed using the ECL reagent provided in the array kit and visualized with ImageQuant LAS4000 (GE Healthcare). ImageQuant TL software was used for pixel quantification. Neurite Sprouting Assay Rat pheochromocytoma (PC12) were seeded at 2 × 10 5 cells/well (ATCC Manassas, VA) on six-well culture dishes coated with 50 mg/mL of collagen type I and 0.1% poly-L-lysine (70-150 kD; Sigma) in RPMI media (Roswell Park Memorial Institute [RPMI] 1640 medium supplemented with 1% antibiotic-antimycotic solution, 5% FBS, and 10% horse serum—all from Gibco/Invitrogen). After cell attachment, control wells were changed to 0.1% serum RPMI media supplemented with 50 ng/mL of recombinant NGF or sterile water vehicle. Remaining wells were subjected to 1.5 mL of conditioned media collected from experiments above (static and HMS cultures). After 4 days, three random phase images per sample were taken from each individual experiment ( n = 3) and the number of neurites per cell body were counted. LIVE/DEAD (Invitrogen) assays images were also conducted. Results: Culture of IVD cells on functionalized silicone did not alter cell viability or homeostasis. HMS upregulated TLR2, TLR4, NGF, and TNF-α gene expression in IVD cells (Fig. 1). Medium from HMS cultures contained elevated levels of GRO, IL-6, IL-8, IL-15, MCP-1, MCP-3, MIG, TGFβ-1, TNF-α, and NGF. Exposure of PC12 cells to HMS-conditioned media resulted in both significantly increased neurite sprouting and cell death. Conclusion: Human AF and NP disc cells were subjected to high-magnitude strains using a novel dynamic culture device coupled to a high-extension silicone rubber culture dish. Gene expression analysis revealed upregulation of TLR2, TLR4, NGF, and TNF message levels. Higher levels of secreted GRO, IL-6, IL-8, IL-15, MCP-1, MCP-3, MIG, TGFb-1, and TNF-α were found in conditioned media. Furthermore, conditioned media from HMS cultures promoted significant neurite outgrowth in PC12 cells. The conditioned media, however, also caused significant increase in cell death compared with static, NGF, and no-NGF controls. Therefore, mechanical strain can directly cause NP and AF cell to secrete factors associated with disc degeneration and discogenic pain, and may have neurotoxic effects. Taken together, this work provides evidence for a direct link between cellular strain, secretory factors, neoinnervation and potential degeneration and discogenic pain in vivo. Disclosure of Interest D. Rosenzweig: None declared R. Gawri: None declared E. Krock: None declared J. Ouellet: None declared L. Stone: None declared T. Quinn: Conflict with Cytomec, makes the stretching device L. Haglund: None declared References Frymoyer JW, Cats-Baril WL. An overview of the incidences and costs of low back pain. Orthop Clin North Am 1991;22(2):263–271 Adams MA, Roughley PJ. What is intervertebral disc degeneration, and what causes it? Spine 2006;31(18):2151–2161 Roughley P, Hoemann C, DesRosiers E, Mwale F, Antoniou J, Alini M. The potential of chitosan-based gels containing intervertebral disc cells for nucleus pulposus supplementation. Biomaterials 2006;27(3):388–396 Rosenzweig DH, Matmati M, Khayat G, Chaudhry S, Hinz B, Quinn TM. Culture of primary bovine chondrocytes on a continuously expanding surface inhibits dedifferentiation. Tissue Eng Part A 2012;18(23-24):2466–2476